A method for designing strong S-Boxes based on chaotic Lorenz system - Ozkaynak, Fatih; Ozer, Ahmet Bedri (Elsevier, 2010)
It is important to design cryptographically strong S-Boxes in order to design secure systems. In this study, a strong, chaos-based S-Box design is proposed. Continuous-time Lorenz system is chosen as the chaotic system. Proposed methodology is analyzed and tested for the following criteria: Bijective property, nonlinearity, strict avalanche criterion, output bits independence criterion and equiprobable input/output XOR distribution. The results of the analysis show that the proposed cryptosystem is a highly reliable system suitable for secure communication. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Chaos; Cryptology; S-Boxes; Lorenz system